Study of the cycle time behavior for product scaling 0.16um and smaller in foundry - Mohd Azizi, Chik; Uda, Hashim, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.